Anthropometric cut-points for discriminating diabetes and the metabolic syndrome among Arabs and Asians: the Kuwait Diabetes Epidemiology Program. Issue 1 (14th January 2022) - Oguoma, Victor M.; Coffee, Neil T.; Alsharrah, Saad; Abu-Farha, Mohamed; Al-Refaei, Faisal H.; Alkandari, Abdullah; Al-Mulla, Fahd; Daniel, Mark
Abstract: This study aimed to determine anthropometric cut-points for screening diabetes and the metabolic syndrome (MetS) in Arab and South Asian ethnic groups in Kuwait and to compare the prevalence of the MetS based on the ethnic-specific waist circumference (WC) cut-point and the International Diabetes Federation (IDF) and American Heart Association/National Heart, Lung, and Blood Institute WC criteria. The national population-based survey data set of diabetes and obesity in Kuwait adults aged 18–60 years was analysed. Age-adjusted logistic regression and receiver operating characteristic (ROC) analyses were conducted to evaluate for 3589 individuals the utility of WC, waist:height ratio (WHtR) and BMI to discriminate both diabetes and ≥3 CVD risk factors. Areas under the ROC curve were similar for WC, WHtR and BMI. In Arab men, WC, WHtR and BMI cut-offs for diabetes were 106 cm, 0·55 and 28 kg/m 2 and for ≥3 CVD risk factors, 97 cm, 0·55 and 28 kg/m 2, respectively. In Arab women, cut-offs for diabetes were 107 cm, 0·65 and 33 kg/m 2 and for ≥3 CVD risk factors, 93 cm, 0·60 and 30 kg/m 2, respectively. WC cut-offs were higher for South Asian women than men. IDF-based WC cut-offs corresponded to a higher prevalence of the MetS across sex and ethnic groups, compared with Kuwait-specific cut-offs. Any of the assessed anthropometric indices can be used in screening of diabetes and ≥3 CVD risk factors in Kuwaiti Arab and Asian populations. ROC values were similar. The WC threshold for screening the MetS in Kuwaiti Arabs and South Asians is higher for women.